Peran Wisata Halal Dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat di Pantai Lon Malang Kabupaten Sampang - Jannah, Raudhotul; Khusnuddin, Khusnuddin (Perbanas Journal of Islamic Economics and Business, 2025)
The tourism sector has a potential economic load that needs to be developed in order toimprove community welfare and regional development evenly because tourism is animportant part of a country's economic development. The benefits obtained from thetourism sector at the macro and micro levels are expected to increase national income andstate foreign exchange sources, in a small scope tourism is expected to create jobs for thecommunity. This study uses a qualitative approach with the aim of researching theimplementation and the benefits of community economic empowerment, also the idealconstruct of community economic empowerment in thematic villages in SampangRegency which has never been observed. The data collection procedure uses observation,interviews, and documentation. The result found that the development of Lon Malangbeach tourism amidst the economic conditions and development of the real sector whichtends to be stagnant, the market potential in the tourism services sector is certainly anopportunity and alternative attraction that must be developed. The tourism sector is anopportunity as well as a challenge for the Bira Tengah Village Government, SampangRegency because this village has potential and tourist attractions that are quite interestingand sell well to regional, national, and international markets. Therefore, the villagegovernment must not only take proactive steps to attract tourists, but also have carefulplanning. Contribution of Lon Malang Tourism in Bira Tengah Village, SokobanahDistrict, Sampang Regency to the Economic Welfare of the Community. Thedevelopment of Lon Malang tourism in Bira Tengah Village, Sokobanah District,Sampang Regency has a positive effect on the expansion of business and employmentopportunities. These business opportunities will provide opportunities for local people towork and at the same time can increase income to support life